TIME BUDGET PRESSURE DAN KARAKTERISTIK PERSONAL AUDITORTERHADAP PERILAKU PREMATURE SIGN-OFF AUDIT PROCEDURES - Faradiza, Sekar Akrom; Chritianto, Januar (Universitas Muhammadiyah Magelang, 2018)
To produce a high quality audit report, an auditor must carry out several audit procedures.Premature sign-off audit procedures is one of the behaviors that can reduce audit quality becauseignores and stops audit procedures that must be carried out in accordance with the audit program.The aims of this research is to examine the effect of time budget pressure and personal auditorcharacteristics on premature sign-off audit procedures. The characteristics considered consist ofexternal locus of control, auditor's self rate performance, turnover intention and self esteem. Inadditions this research also examines the sequence of procedures that are often stopped orabandoned by the auditor. This study used questionnaires to obtained data form 140 auditors inYogyakarta, Semarang and Surakarta. Based on the Friedman test, this research found that theprocedure for understanding client business often ignored by auditors. Based on the logisticregression test, this research found that the time budget pressure factor affects the behavior ofpremature sign-off audit procedures.